A quantitative evaluation of gross versus histologic neuroma formation in a rabbit forelimb amputation model: potential implications for the operative treatment and study of neuromas - Ko, Jason H; Kim, Peter S; O’Shaughnessy, Kristina D; Ding, Xianzhong; Kuiken, Todd A; Dumanian, Gregory A (Journal of Brachial Plexus and Peripheral Nerve Injury, 2011)
Background Surgical treatment of neuromas involves excision of neuromas proximally to the level of grossly “normal” fascicles; however, proximal changes at the axonal level may have both functional and therapeutic implications with regard to amputated nerves. In order to better understand the retrograde “zone of injury” that occurs after nerve transection, we investigated the gross and histologic changes in transected nerves using a rabbit forelimb amputation model.Methods Four New Zealand White rabbits underwent a forelimb amputation with transection and preservation of the median, radial, and ulnar nerves. After 8 weeks, serial sections of the amputated nerves were then obtained in a distal-to-proximal direction toward the brachial plexus. Quantitative histomorphometric analysis was performed on all nerve specimens.Results All nerves demonstrated statistically significant increases in nerve cross-sectional area between treatment and control limbs at the distal nerve end, but these differences were not observed 10 mm more proximal to the neuroma bulb. At the axonal level, an increased number of myelinated fibers were seen at the distal end of all amputated nerves. The number of myelinated fibers progressively decreased in proximal sections, normalizing at 15 mm proximally, or the level of the brachial plexus. The cross-sectional area of myelinated fibers was significantly decreased in all sections of the treatment nerves, indicating that atrophic axonal changes proceed proximally at least to the level of the brachial plexus.Conclusions Morphologic changes at the axonal level extend beyond the region of gross neuroma formation in a distal-to-proximal fashion after nerve transection. This discrepancy between gross and histologic neuromas signifies the need for improved standardization among neuroma models, while also providing a fresh perspective on how we should view neuromas during peripheral nerve surgery.
Keywords: Neuroma; targeted reinnervation; axon reaction; histomorphometry; brachial plexus